Training Counsellors in Gestalt Methods - Greenberg, Leslie S. (Canadian Journal of Counselling and Psychotherapy, 2012)
A training program in the use of the Gestalt two chair method is presented. This approach is based on three components, a knowledge component, a skill training component and an integrating component. The principles of two chair work and the micro- counselling skills required for this training are described and the training approach for their useis discussed. The major themes covered in the training program are outlined and the major Gestalt concepts of awareness, figure/background, introjection, retroflection and projection are discussed. Some of the specific exercises used in the training are presented. In addition, the importance of training the whole person in both skills and attitudes and awareness is discussed.